THE EFFECT ON OVARIAN RESERVE IN THE EARLY POSTOPERATIVE PERIOD IN HYSTERECTOMY ACCORDING TO THE TYPE OF SURGERY - Özden Öztürk; Tayfur Çift; Süleyman Serkan Karaşin (İstanbul Tıp Fakültesi Dergisi)
Objective: The aim of this study was to estimate the possible differential levels of influence of the applied hysterectomy type on ovarian reserve. Materials and Methods: Our study is a single-center prospective cross-sectional study. We included 82 patients who underwent benign hysterectomies between July 2021 and March 2022. There were two groups, abdominal hysterectomy (n=54) and laparoscopic (L/S) hysterectomy (n=28). Transvaginal ultrasonography and hormone status were evaluated before and after the hysterectomy. Patients with a preoperative anti-Mullerian hormone (AMH) value greater than 0.01 ng/dl and a follicle stimulating hormone (FSH) value less than 15 IU/L were included in the study. Results: There was a significant difference between the groups regarding age, parity, duration, and bleeding. There was no significant difference in the percent decrease in AMH value between abdominal and laparoscopic hysterectomies. There was no difference in the comparison regarding the amount of decrease in ovarian volume and antral follicle count (AFS) parameters. In the analysis of serum estradiol values, an increase in 33 patients and a decrease in 49 patients were observed. While serum estradiol values decreased in 33 of 54 patients who underwent abdominal hysterectomy, this rate was 67.3% among patients with decreased estradiol. The difference in estradiol values was not statistically significant. There was a difference between the two groups in the comparative analysis regarding the amount and rate of increase in FSH parameters (p=0.03). Conclusion: In both groups a decrease in ovarian reserve before and after surgery was observed. No significant difference was observed in the analyses performed between them. The increase in FSH levels was more significantly in favor of L/S. Prospective large-scale studies are needed to investigate the effect of L/S hysterectomy on ovarian reserve compared to abdominal surgery, including investigating inhibin-B levels in ovarian follicles due to electrothermal energy use.